2012
DOI: 10.1063/1.4759258
|View full text |Cite
|
Sign up to set email alerts
|

Atomic structure and energy spectrum of Ga(As,P)/GaP heterostructures

Abstract: The atomic structure and energy spectrum of Ga(As,P)/GaP heterostructures were studied. It was shown that the deposition of GaAs of the same nominal thickness leads to the formation of pseudomorphic GaAs/GaP quantum wells (QW), fully relaxed GaAs/GaP self-assembled quantum dots (SAQDs), or pseudomorphic GaAsP/GaP SAQDs depending on the growth temperature. We demonstrate that the atomic structure of Ga(As,P)/GaP heterostructures is ruled by the temperature dependence of adatom diffusion rate and GaAs-GaP interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 60 publications
2
11
0
5
Order By: Relevance
“…We permanently documented that the change of As/P flux ratio does not significantly affect the abruptness of the GaP/GaP 1 − x As x and GaP 1 − x As x /GaP heterointerfaces. Assuming that the catalyst droplet size is constant during the growth, it can be suggested that the heterointerface abruptness is limited by the droplet reservoir effect dominant even for low soluble group‐V elements, rather than group‐V surface interdiffusion across the heterointerface which has a smaller characteristic diffusion length …”
mentioning
confidence: 99%
“…We permanently documented that the change of As/P flux ratio does not significantly affect the abruptness of the GaP/GaP 1 − x As x and GaP 1 − x As x /GaP heterointerfaces. Assuming that the catalyst droplet size is constant during the growth, it can be suggested that the heterointerface abruptness is limited by the droplet reservoir effect dominant even for low soluble group‐V elements, rather than group‐V surface interdiffusion across the heterointerface which has a smaller characteristic diffusion length …”
mentioning
confidence: 99%
“…Проведенные нами расчeты [18] показывают, что энергия локализации электронов в GaAs/GaP КЯ значительно меньше, чем энергия локализации дырок. Это позволяет предполагать, что температурное гашение ФЛ КЯ идeт за счeт делокализации электронов.…”
Section: обсуждение результатовunclassified
“…Аналогичное энергетическое строение с перекрытием электронных и дырочных зон имеют КЯ InSb/GaAs, InSb/AlAs и InSb/AlP. Изученные нами ранее непрямозонные гетероструктуры, выращенные на подложках с ориентацией (001), имеют основное электронное состояние, лежащее в четырехкратно вырожденной X x y -долине зоны проводимости [16,17,19,[21][22][23]25]. Paзличия энергетического спектра гетероструктур, выращенных на подложках с ориентацией (001) и (110), обусловлены изменением распределения деформаций в кристаллической решетке КЯ.…”
Section: результаты и обсуждениеunclassified
“…Существование гетероструктур первого рода с непрямой запрещенной зоной, выращенных на подложках с ориентацией (001), было показано как теоретически [14,15], так и экспериментально [16][17][18][19][20][21][22][23][24][25]. В то же время в литературе практически отсутствуют данные о гетероструктурах, сформированных на подложках с ориентацией (110).…”
Section: Introductionunclassified